ANTIBODI TITER LEVELS IN LOCAL DOGS FOLLOWING RABIES VACCINATION IN PENARUNGAN VILLAGE, MENGWI DISTRICT, BADUNG REGENCY - Petra Rahmitha Sava Setyanto; Ida Bagus Kade Suardana; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Rabies is caused by a virus from the genus Lyssavirus, which belongs to the Rhabdovirus family. In Badung Regency, 13 cases of rabies in dogs were confirmed in 2015, with 8 positive cases reported in Mengwi District. This study aims to measure the antibody titer against the rabies virus in local dogs that had been vaccinated in Penarungan Village, Mengwi District, Badung Regency, seven months after vaccination. The method used in this study was antibody titer testing through the Enzyme-linked Immunosorbent Assay (ELISA). Samples were selected based on inclusion criteria and were collected from Banjar Blungbang, Banjar Cemenggon, Banjar Guming, Banjar Umopoh, and Banjar Bantas. A total of 16 blood samples from local dogs were collected using the venipuncture technique. The results of the study using the ELISA test showed that 12 samples were seropositive, with an average titer value of 0.9 IU/mL, while 4 samples were seronegative, with an average titer value of 0.4 IU/mL. The percentage of seropositive antibody titers in local dogs in Penarungan Village seven months after rabies vaccination was 75%, while the percentage of seronegative antibody titers was 25%. Therefore, booster rabies vaccinations are necessary for dogs with seronegative antibody titers.